Kiểm soát và điều tiết tăng trưởng tín dụng bằng chính sách vĩ mô thận trọng: Bằng chứng thực nghiệm ở Việt Nam - Đinh Thị Thu , Hồng; Nguyễn Hữu , Tuấn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study measures the state of macro-prudential policy in Vietnam and adds empirical evidence to the impact of macro-prudential policy on real credit growth in the Vietnamese market from April 2013 to June 2023. The macro-prudential policy index is measured according to six main components: capital adequacy ratio, 30-day liquidity reserve ratio, credit ceiling regulations, loan-to-deposit ratio, the ratio of state treasury deposits included in the mobilized capital, and the ratio of short-term capital for medium- and long-term loans. The results show that contrary to the trend of loosening monetary policy, Vietnam is tightening its macro-prudential policies. Empirical evidence shows that tightening macroprudential policy tools can help restrict real credit growth and regulate credit in the goods and services production sector.